Analisis Kinerja Keuangan Pemerintah Daerah (Studi Kasus Badan Keuangan Daerah Provinsi Kepulauan Bangka Belitung) - Gayatria Oktalina; Zamhari Zamhari (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
This study is a descriptive quantitative that aims to determine the regional financial performance of the Bangka Belitung Islands Province in 2018-2020 in terms of the degree of fiscal decentralization ratio, regional financial independence ratio, effectiveness ratio, and efficiency ratio along with harmony ratio. The locus of the research at BAKUDA Province of Bangka Belitung. The results of the analysis show that the financial performance of the regional government of the Bangka Belitung Islands Province in terms of (1) The Ratio of Degrees of Fiscal Decentralization is categorized as moderate with an average ratio of 30.78%. (2) Regional Financial Independence Ratio is still relatively low with a consultative relationship pattern with  an  average  ratio  of  46.73%.  (3)  The  PAD Effectiveness Ratio can be categorized as effective because the average ratio is 97.50%. (4) The ratio of regional financial efficiency is less efficient because the average ratio is 95.7%. (5) The compatibility ratio, it can be proven that the provincial government of the Bangka Belitung Islands allocates most of its budget for regional operating expenditures with an average of 72.34% compared to the average capital expenditure of 35.2%.Keywords: Regional Government, Financial Performance